Theoretical and experimental study of active vibration control of rotating composite laminated beams using Fx-NLMS algorithm - Chen, Xiaohong; Sun, Yuxing; Yu, Muhong; Liu, Chunchuan (Mechanical systems and signal processing, 2025)
In the study, an adaptive active vibration control model of rotating composite laminated beam is presented by using the filtered-x normalized least mean square (Fx-NLMS) algorithm, and the experimental study is carried out based on the closed-loop control system. The macro fible composite (MFC) patches is employed to contruct the closed-loop control system of rotating composite laminated beam. By considering peizoelectric coupling effect and the influence of rotating angular velocity, the novel analysis model of vibration transfer function of rotating composite laminated beam with MFC patches is established. The calculation accurancy of the theoretical analysis model is validated by the experimental results. The experimental and simulation studies demonstrate that the low-frequnecy vibration of rotating composite beam is effectively controlled by using the lightweight system. The excellent stability and convergence effect of the closed-loop control system are obtained in the experimental testings. Moreover, the filter orders and learning factor on the active vibration control effect of the rotating composite beam are also stuided and discussed. This work provides a novel appoach for the low-frequency vibration control of the rotating cantilever beams by employing lightweight system.